Vulnerability of the aquifer system from the Nhartanda Valley (City of Tete, Mozambique) - Bande, Ameno Délcio (2019)
Water is an essential resource and must occur in appropriate quantity and quality. The main objective of this research is the vulnerability assessment of the aquifer system in the Nhartanda Valley (City of Tete, Mozambique). Groundwater is collected from the aquifer for the public water supply system of the old city of Tete and a traditional agro-livestock farm, which is irrigated by artesian wells. In situ water determinations and laboratory analysis have been performed to assess water quality in the study area. Groundwater vulnerability was determined through the application of GOD and DRASTIC indexes. The vulnerability indexes of the Nhartanda Valley aquifer vary from moderate-high to very high. During hot and humid seasons, the vulnerability index may reach to extreme levels, being reached relatively quickly by harmful organisms and substances. A specific set of actions and measures are necessary for the protection of the Nhartanda Valley aquifer, which necessarily must involve the social and environmental awareness of civil society and the local population. The better knowledge of the system is essential to support decision-makers on sustainable management of the water resources and protection and remediation strategies for the aquifer. The identification of the most vulnerable areas has generated basic information for that.